Bully - Hirsch, Lee.; Lowen, Cynthia; Anchor Bay Entertainment, Inc.; Weinstein Company; Where We Live Films (Beverly Hills, CA : Anchor Bay Entertainment, 2013)
This is a character-driven documentary following five kids and families over the course of a school year. Offering insight into different facets of America's bullying crisis, the stories include two families who have lost children to suicide and a mother awaiting the fate of her 14-year-old daughter, who has been incarcerated after bringing a gun on her school bus. Documentary provides an intimate and often shocking glimpse into homes, classrooms, cafeterias and principals' offices.
DVD, NTSC, region 1, anamorphic widescreen; Dolby Digital 5.1.
English dialogue with optional Spanish or English subtitles for the hearing impaired.
Cinematography by Lee Hirsch ; edited by Lindsay Utz, Jenny Golden ; music by Ion Furjanic, Bishop Allen.
Videodisc release of the 2011 documentary film.
MPAA rating: PG-13; for "intense thematic material, disturbing content, and some strong language--all involving kids"--Container.
Special features: deleted scenes; The Bully project at work; Mex after Bully; Mex's character sketch; Mex raps; Keloy's original sketch; Meryl Streep on bullying; Communities in motion; Sioux City after Bully; Good Morning America; Kevin Jennings : an advocate's perspective; Bully : the book.
Keywords: Bullying -- United States; Bullying in schools -- United States; Bullying -- Prevention; Bullying in schools -- Prevention; Bullying -- United States; Schools -- United States; Students -- psychology; Acoso -- Estados Unidos; Acoso en las esculas -- Estados Unidos; Documentary films; Nonfiction films; Feature films; Video recordings for the hearing impaired